2015
DOI: 10.1007/s00784-015-1605-2
|View full text |Cite
|
Sign up to set email alerts
|

Removal of simulated biofilm: a preclinical ergonomic comparison of instruments and operators

Abstract: The use of hand instruments has potential ergonomic disadvantages. However, with increasing experience, operators are able to recognise and mitigate possible risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Furthermore, in this study, power-driven instruments led to significantly better results than manual curettes. In a previous study, Graetz et al [ 21 ] observed that practitioners handling power-driven instruments work more ergonomically than those using hand instruments, irrespective of the operator’s level of experience. In addition to that, the use of hand instruments was described as more tiresome and demanding.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this study, power-driven instruments led to significantly better results than manual curettes. In a previous study, Graetz et al [ 21 ] observed that practitioners handling power-driven instruments work more ergonomically than those using hand instruments, irrespective of the operator’s level of experience. In addition to that, the use of hand instruments was described as more tiresome and demanding.…”
Section: Discussionmentioning
confidence: 99%
“…The only scientific proven advantage of (ultra)sonic instrumentation is that it is time saving and less labor intensive [8]. It is 20% to 50% faster than hand instrumentation [9][10][11][12][13][14][15] and leads to less wrist deviation and inclination of head and neck (potentially leading to musculoskeletal problems) [16]. Additionally, hand instruments are also experienced as more tiring than (ultra) sonic instruments [16].…”
Section: Introductionmentioning
confidence: 99%